Longitudinal Comparison of Stability and Sensitivity in Quality of Life Scores Among Nursing Home Residents With and Without Diagnoses of Alzheimer's Disease and Related Dementias. Issue 3 (21st July 2021) - Qin, Xuanzi; Baker, Zachary G; Jarosek, Stephanie; Woodhouse, Mark; Chu, Haitao; McCarthy, Teresa; Shippee, Tetyana P
Abstract: Background and Objectives: Prevalence of nursing home residents with Alzheimer's disease and related dementias (ADRD) has increased along with a growing consensus that person-centered ADRD care in nursing homes should maximize quality of life (QoL). However, concerns about whether residents with ADRD can make appropriate QoL judgments persist. This study assesses the stability and sensitivity of a self-reported, multidomain well-being QoL measure for nursing home residents with and without ADRD. Research Design and Methods: This study linked the 2012–2015 Minnesota Nursing Home Resident QoL and Satisfaction with Care Survey, Minimum Data Set 3.0 (nursing home assessments), and Minnesota Department of Human Services Cost Reports. The QoL survey included cohort–resident pairs who participated for 2 consecutive years ( N = 12 949; 8 803 unique residents from 2012–2013, 2013–2014, and 2014–2015 cohorts). Change in QoL between 2 years was conceptualized as stable when within 1.5 SD of the sample average. We used linear probability models to estimate associations of ADRD/Cognitive Function Scale status with the stability of QoL summary and domain scores (eg, social engagement) and the absolute change in QoL summary score, controlling for resident and facility characteristics. Results: Most (86.82%) residents had stable QoL summary scores. Residents with moderate to severe cognitive impairment, irrespective of ADRD, were less likely to have stable summary scores than cognitively capable residents without ADRD ( p < .001), but associations varied by QoL domains. Among those with stable summary QoL scores, changes in health/functional status were associated with absolute changes in summary QoL score ( p < .001), suggesting sensitivity of the QoL measure. Discussion and Implications: QoL scores were similarly stable over time for most residents with and without ADRD diagnoses and were sensitive to changes in health/functional status. This self-reported QoL measure may be appropriate for nursing home residents, regardless of ADRD diagnosis, and can efficaciously be recommended to other states.